Computational investigation and optimisation study on system performance of heat sink using perforated pin fins mounted at different angles. (9th October 2019) - Maji, Ambarish; Bhanja, Dipankar; Patowari, Promod Kumar
The current work investigates the performance of heat sink using perforated pin fins of different shapes with various perforation geometries like circular, diamond shaped and elliptical type. Three dimensional CFD simulations have been performed to explore the effects of fin shape, perforation geometry and perforation size on system performance. This work also analyses the variations in heat transfer enhancement through elliptical and square shaped staggered pin fins with elliptical perforations mounted at different angular position on the path of the flow. Multi Objective Optimisation under Ratio Analysis is applied to select the best heat sink configuration. Exergy efficiencies, entropy generations and irreversibilities are also calculated for all the fin shapes having various sizes of perforations. It is observed that heat transfer rate of perforated fins up to certain perforation number and size are always greater than their solid counterparts and with the change in perforation geometry and fin shape heat dissipation rate enhances significantly.